2021
DOI: 10.3390/biom11060876
|View full text |Cite
|
Sign up to set email alerts
|

Hyperactivated RAGE in Comorbidities as a Risk Factor for Severe COVID-19—The Role of RAGE-RAS Crosstalk

Abstract: The receptor for advanced glycation-end products (RAGE) is a multiligand receptor with a role in inflammatory and pulmonary pathologies. Hyperactivation of RAGE by its ligands has been reported to sustain inflammation and oxidative stress in common comorbidities of severe COVID-19. RAGE is essential to the deleterious effects of the renin–angiotensin system (RAS), which participates in infection and multiorgan injury in COVID-19 patients. Thus, RAGE might be a major player in severe COVID-19, and appears to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 137 publications
1
37
0
Order By: Relevance
“…Recent studies have suggested the activation of an HMGB1-RAGE cascade in COVID-19 pathogenesis [56] , [57] and an association with disease severity [21] , [58] . In this respect, our results showed an overexpression of HMGB1 and RAGE proteins in the plasma of patients with COVID-19, confirming that this effect is a common finding in the most severe forms of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have suggested the activation of an HMGB1-RAGE cascade in COVID-19 pathogenesis [56] , [57] and an association with disease severity [21] , [58] . In this respect, our results showed an overexpression of HMGB1 and RAGE proteins in the plasma of patients with COVID-19, confirming that this effect is a common finding in the most severe forms of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…The RAGE interacts with effectors of the renin–angiotensin system (RAS), promoting the progression of a “cytokine storm” in macrophages and splenocytes; causing endothelial dysfunction on account of increased capillary permeability and release of damage-associated molecular pattern components (DAMP); increasing the production of ROS and the formation of atherosclerotic plaques; increasing the risk of thrombosis by inducing the formation and release of extracellular traps by neutrophils (NET), with further thrombocyte aggregation; and causing muscle wasting, stimulating apoptosis, increasing protein degradation and decreasing protein synthesis. The combined effects of RAGEs and AT1R occur in the vessels and parenchyma of the lungs, brain, heart and kidneys, and in the cells of the immune system, causing irreversible damage to many organs [ 259 ]. The question of what is still primary (cause) and what is secondary (consequence), in this case, not only has the right to be asked, but deserves serious attention on the part of scientists and physicians.…”
Section: Role Of Modified Albumin In Pathogenesis Of Diseasesmentioning
confidence: 99%
“…HMGB-1 is a damage-associated molecular pattern protein that, when is secreted by damaged cells, exerts a strongly inflammatory activity binding to receptors as receptor for advanced glycation end products (RAGE) and Toll-like receptors 3 and 4. The link between HMGB-1 and thrombosis appears to be focused on the interaction with platelets, NET and coagulation and fibrinolysis factors [ 42 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have proposed that the presence of aPL and thrombotic events in COVID-19 patients could represent a secondary form of APS [ 52 , 53 ]. The aPL associated with secondary APS caused by infections usually disappeared in a short period of time [ 7 , 43 , 44 , 45 ]. Xiao et al propose that the dynamics of aPL in COVID-19 are similar to those in other infections [ 20 ].…”
Section: Discussionmentioning
confidence: 99%